Leveraging Emergency Department Information Systems to Address Palliative Care Needs of ED Patients During the COVID Pandemic. (May 2022) - Tan, Audrey J.; Swartz, Jordan; Wilkins, Christine; Grudzen, Corita
The arrival of the COVID-19 pandemic to hospitals in New York City stressed our emergency departments (ED) with high patient volume, stresses on hospital resources and the arrival of numerous high acuity, critically ill patients. Amid this time, we sought to leverage the ED Information Systems (EDIS), to assist in connecting critically ill patients, their families, and providers in the ED with palliative care resources. We discuss 4 innovative, thoughtful solutions to assist ED providers in identifying and addressing the acute and unique palliative care needs of COVID patients.